Challenges and Pathways in Developing Dual-Qualified Teaching Staff for Higher Vocational Film and Television Majors - WuLiSha; Liu Rong (Journal of Exploration of Vocational Education, 2025)
In recent years, China’s vocational education has entered a new stage of quality improvement and value-added empowerment. Shandong Vocational College of Cultural Industries currently faces practical problems such as misalignment between recognition standards and industry realities, insufficient efficacy of training mechanisms, weak incentives for school–enterprise collaboration, and skewed evaluation and reward orientations. At root, these issues stem from the inherent tension between the stability of education and the rapid iteration of industry, as well as the absence of deep school–enterprise collaboration mechanisms. In response, this paper proposes a systematized “standards–mechanisms–evaluation” triadic pathway, aiming to provide pragmatic, workable solutions for building “dual-qualified” faculty in film and television programs.